Multiple Solutions for the Discrete p-Laplacian Boundary Value Problems - Yuhua Long; Haiping Shi (Discrete Dynamics in Nature and Society)
By employing a critical point theorem, established by Bonanno, we prove the existence of three distinct solutions to boundary value problems of nonlinear difference equations with a discrete p-Laplacian operator. To demonstrate the applicability of our results, we also present an example.